One year experience of OMOM Capsule Endoscopy for suspected intestine lesions - Khadka, Mohan; Tao, Xiaohong; Chen, Dao-Rong; Wang, Shun-Wen; Gu, Sai (Journal of Nobel Medical College, 2012)
Background: Capsule endoscopy (CE), is a superior non-invasive tool in the diagnosis of suspected small bowel lesions to conventional modalities. This study has been carried out with the aim to share the experience and to evaluate the efficacy of OMOM CE. The objectives have been set to find out and compare the diagnostic yields of the CE for obscure gastrointestinal bleeding (OGB) and unexplained abdominal pain and/or diarrhea and also to see the cost effectiveness and quality of the CE. Methods: OMOM CE examination was conducted in consecutive 46 admitted patients presented with suspected small intestinal lesions over a period of one year. The indications were OGB, unexplained abdominal pain and diarrhea. Results: Abnormal findings were revealed in 42 out of which 36 subjects revealed significant abnormal findings in small bowel. Overall diagnostic efficacy of the CE was 80% and Diagnostic yield was significantly higher for OGB (26/27) in comparison to unexplained abdominal pain and/or diarrhea (96.30% vs 55.55%, P < 0.001). Angioectasia was the major finding for OGB cases. No complications were observed with the CE examination. Conclusion: OMOM CE has high diagnostic yield for OGB and unexplained abdominal pain or diarrhea and effectiveness is comparable with Pillcam CE. DOI: http://dx.doi.org/10.3126/jonmc.v1i1.7285 Journal of Nobel Medical College Vol.1(1) 2011 27-39